2018
DOI: 10.4067/s0718-95162018005001001
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield, quality traits and grain yield stability of local oat cultivars

Abstract: This study was conducted to define grain yield and quality traits of local oat cultivars and to assess the adaptability to and stability of cultivars in different environments of Central and West Black Sea Region of Turkey.Twenty-five oat genotypes were evaluated in a randomized block design with four replications in six different environments. Genotype, environment and genotype × environment interaction had highly significant effects on grain yield and quality traits. The oat genotypes exhibited significant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 17 publications
2
43
3
2
Order By: Relevance
“…Protein content is a primary quality indicator for corn grains. Mut et al [33] and Peterson et al [34] reported that the grain protein content changed from 3 to 4% and 10.0 to 18.0%, respectively within different oat genotypes cultivated in different environments. The protein content was mainly affected by the environment rather than the genotype.…”
Section: Quality Characteristics Of Harvested Corn Grainsmentioning
confidence: 99%
“…Protein content is a primary quality indicator for corn grains. Mut et al [33] and Peterson et al [34] reported that the grain protein content changed from 3 to 4% and 10.0 to 18.0%, respectively within different oat genotypes cultivated in different environments. The protein content was mainly affected by the environment rather than the genotype.…”
Section: Quality Characteristics Of Harvested Corn Grainsmentioning
confidence: 99%
“…Dužina trajanja perioda nalivanja zrna nalazi se pod značajnim uticajem ekoloških faktora, pre svega visokih temperatura koje skraćuju ovaj period (Hurkman and Wood, 2011). Selekcijom genotipova koji ranije cvetaju može se uticati na formiranje većeg broja cvetova -potencijalnog akceptora asimilata i duži period nalivanja zrna, odnosno izbor prinosnijih genotipova (Mut et al, 2018).…”
Section: Uvodunclassified
“…Ключевым вопросом адаптивной селекции является проблема учета взаимодействия генотипа и среды. Отбор в одних условиях может не обеспечивать преимущества генотипов в других, что делает актуальным получение информации о генотипах и средах на ранних этапах селекции [7][8][9].…”
Section: Introductionunclassified